The Influence of Product Quality and Promotion on Customer Satisfaction CV. Bogor City Bloods - Fadillah, Eki Ahmad; Andari, Titiek Tjahja; Pramestidewi, Chandra Ayu (MultiTech Publisher, 2024)
This research aims to find out and identify product quality and promotions both simultaneously and partially on CV customer satisfaction. Bogor City Bloods. The sample size was 100 respondents taken using purposive sampling technique, namely a technique for determining samples with certain considerations. The questionnaire was tested using validity tests, reliability tests and classical assumption tests. The results of this test are valid, reliable, and can be used for regression data. The analytical method used in this research is descriptive and verification with a quantitative approach. The research results show that product quality and promotion variables, both simultaneously and partially, have a positive and significant effect on customer satisfaction. The test results for the coefficient of determination R (square) were 40%, while the remainder was 60%. The relationship between product quality and promotion is strong in the same direction with a correlation coefficient of 0.638.